Perception of Individual Investor towards Financial Statement: A Study of Nepalese Stock Market - Maharjan, Ricky (MVIC Journal of Management and Information Technology, 2025)
This study investigates the perceptions of individual investors towards financial statements in Nepal's stock market using a descriptive research design. A quantitative approach was employed, with a researcher-administered, questionnaire-based survey conducted among 100 respondents out of 135 distributed questionnaires (74.07% response rate). Data were gathered from ten brokerage firms in Kathmandu, with a sample diverse in age, gender, education, occupation, and income. The questionnaire addressed demographic profiles, investment experience, and perceptions of financial statements, evaluating key attributes like understandability, reliability, relevance, and decision-making usefulness on a 5-point Likert scale. The findings revealed that 73% of respondents were male, with the majority (45%) in the 36-50 age group. Half of the respondents had a Bachelor’s degree, and 44% earned over NPR 40,000 monthly. Respondents found financial statements moderately understandable (mean score 3.68), with the income statement being the most understandable. Reliability was also rated moderately (mean score 3.11), with the income statement and balance sheet viewed as more reliable. Financial statements were deemed somewhat relevant (mean score 3.15), with the income statement again rated highest. Perceived decision-making usefulness scored moderately (mean score 3.23), with the income statement rated as the most useful. Strong positive correlations were found between the use of financial statements and their perceived attributes, emphasizing the value of frequent usage for better decision-making.